(untitled) (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT The House of the Divine, situated in Ponta Grossa (PR), was tumbled by Municipal Council of Artistic and Cultural Heritage (COMPAC) in 2004. With religious activities since 1882, is consider a cultural historical heritage of city and have characteristics constituting a space of expression the popular catholic religiosity. The proposal of this article is from this official recognition of the House of the Divine as material heritage and as a space of devotional practices, such as the Feast of the Divine, understand it as an immaterial heritage. The theoretical-methodological context to present brief description about cultural heritage, well as relation between identity and the photographic record. The photography is understood while representations not just of real, but so that symbolic, given that the images to extrapolate that what is visible. KEY-WORDS House of the Divine; Cultural heritage; Popular culture; Identity; Photography.